Penegakan Hukum Terhadap Pelanggaran Pembuangan Sampah di Daerah Aliran Sungai Pangkalpinang - Yuanda Rarindalia Widodo; Rizca Aulia Ambarsari P.M; Cherry Gladicca; Aisyah Danies; Laura Safira Diniarti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the extent to which the implementation of Pangkalpinang City Regional Regulation Number 6 of 2013 on Waste Management has reduced the volume of waste contributing to flooding, and to identify efforts to improve its effectiveness. The research employs an empirical juridical method, combining legal analysis of the regulation with field findings obtained through interviews with the Environmental Agency of Pangkalpinang City. The results indicate that the regulation has been implemented through waste collection, transportation, and processing activities at TPS 3R and the final disposal site (TPA). However, its effectiveness remains limited due to low public awareness, inadequate facilities, insufficient socialization, and weak supervision. To improve its implementation, it is necessary to strengthen public education, expand waste management infrastructure, enforce stricter regulations, and enhance inter-agency cooperation between the Environmental Agency, Public Works Office, and local governments.